Territorial solar baking potential: A socio-technical analysis for planning the sustainable energy transition of the bakery world - Guillaume Guimbretière; Benjamin Pillot; Christophe Révillion; Corrie Mathiak; Romain Authier (Cleaner and Responsible Consumption)
Nowadays, for energy reasons bread consumption appears unsustainable in the long-term. Direct solar baking can be part of the solution, but tools allowing for the estimation of the social-technical potential of solar baking at the territorial scale are lacking. In this article a socio-technical solar bakery’s workflow model and two socio-economic indicators were developed. Then, these numeric tools were used in the frame of a full solar production and soft mobility scenario in a small tropical island (Réunion, France). Results show that in the best sites solar baking can be performed at least once a week with a production up to 16 tons/year and ≈ 32,000 tCO2 emissions per year could be saved.